Influence of Weather Conditions on the Incidence of SAH - da Silva, Vinícius Otávio; Manicardi, Rafaela Pádua; da Silva, Brenda Martins; Pereira, Carlos Umberto; Rabelo, Nícollas Nunes (Arquivos brasileiros de neurocirurgia, 2025)
Subarachnoid hemorrhage (SAH) is a clinical condition in which there is bleeding into the subarachnoid space, and it is known that there are modifiable risk factors, such as high blood pressure and smoking. However, specific meteorological conditions, such as temperature and atmospheric pressure, have also been observed to represent a higher risk for this condition. The objective of this systematic review was to synthesize the current literature data on the relationship between meteorological factors and the occurrence of SAH. Following PRISMA guidelines, the review investigated the impact of meteorological conditions on the incidence of subarachnoid hemorrhage, with the guiding question: "What is the relationship between climate variations and SAH cases?" through comprehensive searches in academic sources with studies published between 2013 and 2023 in the PubMed and BVS (Virtual Health Library) databases. The main variables evaluated were daily average temperature, average atmospheric pressure, relative humidity, wind speed, influenza incidence, solar incidence, partial oxygen pressure, seasonal distribution, and seasons of the year. The study highlighted the influence of meteorological conditions on the occurrence of subarachnoid hemorrhage (SAH), especially in cases of extreme climate variations and high atmospheric pressure.